PENYELESAIAN DELIK PERZINAHAN MELALUI ADAT SERAWAI DI DESA PADANG PELAWI KABUPATEN BENGKULU SELATAN - Arju Sethiawanza; Muhammad Alvin Sandjaya; Muhammad Micola Valito; Nizam Tazmi (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This study aims to determine and analyze the qualifications of adultery crimes in the customary law system in Indonesia. To determine and analyze the settlement of adultery crimes through the Serawai customary law mechanism. The research method used in this study uses empirical legal research and an empirical legal approach, namely a non-doctrinal approach. The results of the study regarding the settlement of customary violations related to adultery in the Serawai Bengkulu Selatan custom are reports from residents, reports to the village head, summons or notification of customary officials, customary hearings, decisions of deliberations at the customary council, and implementation of customary ceremonies. The form of sanctions for customary violations related to adultery according to the Serawai Bengkulu Selatan custom is that the perpetrator of the customary violation apologizes to the community for the actions he has committed, makes a letter of agreement that aims for the perpetrator not to repeat his actions again and gives a warning to others so that the same violation does not occur, pays customary fines, cleans the village, marries, and is expelled or exiled to another area. Penelitian ini bertujuan Untuk mengetahui dan menganalisis kualifikasi delik perzinaan dalam sistem hukum Adat di Indonesia. Untuk mengetahui dan menganalisis Penyelesaian Delik perzinaan melalui mekanisme Hukum Adat Serawai. Metode penelitian yang digunakan dalam penelitian ini menggunakan penelitian hukum empiris dan pendekatan hukum empiris yaitu pendekatan nondoktrinal. Hasil penelitian mengenai penyelesaian pelanggaran adat yang berkaitan dengan perzinahan adat Serawai Bengkulu Selatan adalah laporan dari warga, laporan kepada kepala desa, pemanggilan atau pemberitahuan pejabat adat, sidang adat, keputusan musyawarah pada dewan adat, dan pelaksanaan upacara adat. Bentuk sanksi pelanggaran adat yang berkaitan dengan pezinahan menurut adat Serawai Bengkulu Selata yaitu, pelaku pelanggaran adat meminta maaf kepada masyarakat atas perbuatan yang telah dilakukannya, membuat surat perjanjian yang bertujuan agar pelaku tidak mengulangi perbuatannya lagi dan memberikan teguran kepada orang lain agar tidak terjadi pelanggaran yang sama, membayar denda adat, cuci kampung, menikahkan, dan diusir atau dibuang ke daerah lain.